PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERASI - Raningsih, Ni Kadek; Artini, Luh Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.08.TAHUN 2018DO - 10.24843/EEB.2018.v07.i08.p03, 2018)
The result of this study indicates that profitability has positive effect on the corporate value. Economic and Social CSR weaken the effect of probability on the corporate value; meanwhile Environmental CSR was not able to moderate the influence of probability on the corporate value.The population in this study is manufacturing company in Indonesia Stock Exchange in the period 2013-2016. Non-probability method was used as sample determination with purposive sampling technique and 12 manufacturing companies was obtained with total observation of 48. Analysis technique that was used is moderation regression analysis.  The practical implication that can be given from the findings of this study is that, this study can be the baseline in motivating the company to improve the total assets of the company because assets show the assets used for the company’s operational activities that can improve profitability therefore can increase the corporate value.